Analisis Praktik Belajar dari Rumah Kelas VI SD Gayamsari 02 Semarang di Masa Pandemi COVID-19 - Yuniarti, Lania; Saputra, Henry Januar; Budiman, M. Arief (STKIP Andi Matappa Pangkep, 2021)
The aim of this study was to find out how the practice learning from home for class VI SDN Gayamsari 02 Semarang during COVID-19 pandemic could be implemented. The type of research used is a qualitative method with descriptive approach. This study uses several methods to collect data, including: interviews, observations, questionnaires and documentation. The data analysis technique used is triangulation technique. Results of this study indicate that Class VI students SDN Gayamsari 02 carry out learning at home accompanied by parents/family members/tutors.Â In one week students study from home 5-6 days with an average of 1-2 hours every day. Implementing learning from home that is taught by teachers to students is by communicating via WhatsApp, providing learning videos, assignments, making projects/creativity practices, and online learning through zoom/google meet application. Social media that are most often used to help by students during learning are whatsapp and youtube. Obstacles experienced by students are lack of concentration, difficulty understanding lesson, students feel bored and cannot ask questions directly to teacher. Support provided by the school while studying from home is by providing internet data packages and lending books. Internet facilities and student devices are also available and can be used properly.